'Trial and error…', '…happy patients' and '…an old toy in the cupboard': a qualitative investigation of factors that influence practitioners in their prescription of foot orthoses. Issue 1 (December 2016) - Williams, Anita; Martinez-Santos, Ana; McAdam, Jane; Nester, Christopher
Abstract Background Foot orthoses are used to manage of a plethora of lower limb conditions. However, whilst the theoretical foundations might be relatively consistent, actual practices and therefore the experience of patients is likely to be less so. The factors that affect the prescription decisions that practitioners make about individual patients is unknown and hence the way in which clinical experience interacts with knowledge from training is not understood. Further, other influences on orthotic practice may include the adoption (or not) of technology. Hence the aim of this study was to explore, for the first time, the influences on orthotic practice. Methods A qualitative approach was adopted utilising two focus groups (16 consenting participants in total; 15 podiatrists and 1 orthotist) in order to collect the data. An opening question"What factors influence your orthotic practice?" was followed with trigger questions, which were used to maintain focus. The dialogue was recorded digitally, transcribed verbatim and a thematic framework was used to analyse the data. Results There were five themes: (i) influences on current practice, (ii) components of current practice, (iii) barriers to technology being used in clinical practice, (iv) how technology could enhance foot orthoses prescription and measurement of outcomes, and (v) how technology could provide information for practitioners and patients. A final global theme was agreed by the researchers and the participants: 'Current orthotic practice is variable and does not embrace technology as it is perceived as being not fit for purpose in the clinical environment. However, practitioners do have a desire for technology that is usable and enhances patient focussed assessment, the interventions, the clinical outcomes and the patient's engagement throughout these processes'. Conclusions In relation to prescribing foot orthoses, practice varies considerably due to multiple influences. Measurement of outcomes from orthotic practice is a priority but there are no current norms for achieving this. There have been attempts by practitioners to integrate technology into their practice, but with largely negative experiences. The process of technology development needs to improve and have a more practice, rather than technology focus.